The Audiovisual Research Collection for Performing Arts (ARCPA) at Universiti Putra Malaysia: negotiating ethical issues in social sciences - Musib, Ahmad Faudzi; Jahnichen, Gisa; Meddegoda, Chinthaka Prageet (International Association of Sound and Audiovisual Archives, 2014)
The article focuses on a study related to Audiovisual Research Collection for Performing Arts (ARCPA) and its relevance to Universiti Putra Malaysia discussing ethical issues in social sciences. Topics include research on impact of audiovisual (AV) archive materials on creative art works, no alteration of copyright and legal status or resulting claims of the archivals through the archiving process, data integration designs for music recordings, and digital preservation using digital recorders.